An enzyme-responsive controlled release system of mesoporous silica coated with Konjac oligosaccharide - Guo, Wei (Langmuir : the ACS journal of surfaces and colloids, 2014)
A simple and green method to fabricate an ingenious enzyme-responsive drug controlled release system was presented. Mesoporous silica material (mSiO2) 100 nm in size was used as the host, and Konjac oligosaccharide (KOGC) was employed to seal the nanopores of mSiO2 to inhibit the drug release. Rhodamine B was used as the model cargo to reveal the release behavior of the system. The KOGC-modified mSiO2 (mSiO2KOGC) retains the drug until it reaches the colonic environment where bacteria secrete enzymes (β-mannanase) can degrade KOGC and make drug release. The amount of KOGC and enzyme can be used to adjust the release performance. And all the release behaviors fit the two-step Higuchi model, which predominate by KOGC degradation and mesoporous structure, respectively. With well bioactivity and selectivity, the system has potential application as an oral medicine carrier for treating intestinal disease